2022
DOI: 10.1021/acsami.1c14720
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and Outdoor Testing of Perovskite Solar Cells: Comparing Industrially Relevant Process with a Simplified Lab Procedure

Abstract: Perovskite solar cells (PSCs) have shown great potential for next-generation photovoltaics. One of the main barriers to their commercial use is their poor long-term stability under ambient conditions and, in particular, their sensitivity to moisture and oxygen. Therefore, several encapsulation strategies are being developed in an attempt to improve the stability of PSCs in a humid environment. The lack of common testing procedures makes the comparison of encapsulation strategies challenging. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 46 publications
(94 reference statements)
1
52
0
Order By: Relevance
“…These results further demonstrate that the outdoor spectral red shift in the morning and evening hours contributes to the PV enhancement of the PSC system, because it increases the ratio of available energy. Similar PR changes have also been reported in literature on the outdoor stability of PSCs, [ 21 ] but no in‐depth research has been carried out on this point. In addition, interestingly, although the irradiance and ER are basically close, the PR of the PSC in the evening is significantly higher than in the morning.…”
Section: Resultssupporting
confidence: 81%
“…These results further demonstrate that the outdoor spectral red shift in the morning and evening hours contributes to the PV enhancement of the PSC system, because it increases the ratio of available energy. Similar PR changes have also been reported in literature on the outdoor stability of PSCs, [ 21 ] but no in‐depth research has been carried out on this point. In addition, interestingly, although the irradiance and ER are basically close, the PR of the PSC in the evening is significantly higher than in the morning.…”
Section: Resultssupporting
confidence: 81%
“…[ 77 ] Emery et al compared the “LAB” encapsulation method using UV‐glue with “COM” using POE hot press and butyl rubber edge sealing, which showed the “COM” encapsulation scheme can pass the IEC 61215 damp heat test. [ 182 ]…”
Section: Stability Test Protocols Of Pscs Under Combined Elevated Tem...mentioning
confidence: 99%
“…[77] Emery et al compared the "LAB" encapsulation method using UV-glue with "COM" using POE hot press and butyl rubber edge sealing, which showed the "COM" encapsulation scheme can pass the IEC 61215 damp heat test. [182] Through the analysis of these successful 85% RH/85 °C aging test cases, it can be found that several aspects play a crucial role in passing the damp heat aging test. First, a stable perovskite component containing FA, Cs was proposed.…”
Section: % Rh/85 °C Aging Testmentioning
confidence: 99%
“…Although encapsulation can effectively protect the devices from moisture and oxygen, it cannot completely tackle the challenge of thermal‐induced degradation. [ 8,9 ] Further research is, therefore, urgently needed to improve the instinct thermal stability of all‐perovskite tandem solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although encapsulation can effectively protect the devices from moisture and oxygen, it cannot completely tackle the challenge of thermal-induced degradation. [8,9] Further research is, therefore, urgently needed to improve the instinct thermal stability of all-perovskite tandem solar cells.The thermal stability and performance of mixed Pb-Sn PSCs can be influenced by manipulating the composition of the perovskite, especially the A-site cation. [10][11][12][13] Currently, the efficient mixed Pb-Sn narrow-bandgap (NBG) PSCs are primarily achieved by the incorporation of MA cation (>30%).…”
mentioning
confidence: 99%